Agricultural Communicators in Education - Jim Shaner; Don Esslinger (Journal of Applied Communications, 1980)
Editorial back matter for vol.64, no.1, Jan-Mar (1980) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education